2021
DOI: 10.1016/j.jsbmb.2020.105794
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid biosynthesis in Smith-Lemli-Opitz syndrome bypassing cholesterol: Potential importance of pathway intermediates

Abstract: Highlights New pathway of bile acid biosynthesis avoiding cholesterol. Mechanism for biosynthesis of 3β,7β-dihydroxy-5-ene bile acids. Biosynthesis of 3β-hydroxy-7-oxo-5-ene bile acids. Pathway intermediates bind to and activate Smo. A new link between SLOS and deranged Hh signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…However, oxysterols have roles beyond cholesterol per se and can act as ligands to G proteincoupled receptors (GPCR; Hannedouche et al, 2011;Liu et al, 2011). One GPCR that oxysterols and cholesterol activate is Smoothened (SMO), a critical receptor in the Hedgehog (Hh) signalling pathway (Abdel-Khalik et al, 2020;Radhakrishnan et al, 2020). Like in cholesterol regulation and in protection against microbial infection, oxysterols and accessible cholesterol are closely linked in the Hh signalling pathway.…”
Section: Oxysterols Accessible Cholesterol and Hedgehog Signallingmentioning
confidence: 99%
See 4 more Smart Citations
“…However, oxysterols have roles beyond cholesterol per se and can act as ligands to G proteincoupled receptors (GPCR; Hannedouche et al, 2011;Liu et al, 2011). One GPCR that oxysterols and cholesterol activate is Smoothened (SMO), a critical receptor in the Hedgehog (Hh) signalling pathway (Abdel-Khalik et al, 2020;Radhakrishnan et al, 2020). Like in cholesterol regulation and in protection against microbial infection, oxysterols and accessible cholesterol are closely linked in the Hh signalling pathway.…”
Section: Oxysterols Accessible Cholesterol and Hedgehog Signallingmentioning
confidence: 99%
“…The components for Hh signalling are found in primary cilia, antenna-like organelles which are continuous with the plasma membrane (Rohatgi et al, 2007). Side-chain oxysterols are potential second messengers in the Hh pathway, in that they activate Hh signalling in cultured cells, even in the absence of SHH, and induce the accumulation of SMO in primary cilia (Corcoran and Scott, 2006;Dwyer et al, 2007;Nachtergaele et al, 2012;Abdel-Khalik et al, 2020). Side-chain oxysterols bind to the extracellular cysteine-rich domain (CRD) of SMO (Myers et al, 2013;Nachtergaele et al, 2013;Nedelcu et al, 2013;Abdel-Khalik et al, 2020) and have also been found to be enriched in primary cilia (Raleigh et al, 2018).…”
Section: Oxysterols and The Hedgehog Signalling Pathwaymentioning
confidence: 99%
See 3 more Smart Citations